Effect of Profitability, Size And Debt Policy To Company Value (Study on Business-27 Company Listed On BEI) - Ary Meizari; Tri Okta Viani (Proceeding International Conference on Information Technology and Business, 2017)
Firm Value is influenced by the financial performance of a company. Financial performance is reflected by stock prices and shown in a good performance as well as how the company uses its assets to get maximum profit. The purpose of this study wasto determine the impact of profitability, size, and debt policy to firm value on companies in business27 index at the Indonesia Stock Exchange. The analysis of the data used in this research was multiple linear regression. The result showed that the profitability had significant effect on value of firm. The size had significant effect on firm value. The debt policy had significant effect on firm value. The F test results showed that Profitability, Size and Debt Policy had significant effect on firm value at the companies in business27 index atthe Indonesia Stock Exchange. Keywords: Profitability, Size, Debt Policy, andCorporate Value.